CHILDHOOD OBESITY - BMI AND PARENTS' SPEECH (Fiep Bulletin - online, 2011)
In developed countries, obesity is considered a public health problem, and the World Health Organization considered as global epidemic. Excess body weight is not just a cosmetic problem but also is directly linked to health risk factors due to industrialization and the lifestyle of the population, which might characterize the situation as a global epidemic (WHO). In Brazil, obesity is growing too, and the rate of increase in the very young (child) are similar to that found in more developed countries. This study was designed to determine the prevalence of overweight and obesity in children age 7-9 years, studens in private school, located in Madurai district in the north of Rio de Janeiro, and through parents information identify the factors that may have direct or indirect generated interference in this obesity. Besides the measurement of BMI was used instrument with theoretical questions that were answered by 50 parents of children that had a average age of 7.74 ± 0.80 years. Had a mean body mass index (BMI) of 17.90 ± 3.40 kg/m2. Obesity were not found in girls, but the ones with 7 and 9 years were overweight. The same happens with the boys, except for the eight years old ones who were within the standard referenced by ABESO. In the study group for parents information denotes the existence of influence of their behavior in the presence or absence of obesity. Information from parents shows that the characteristic lifestyle of their children is directly related to them.
Keywords: BMI; Childhood obesity; Parents address